Effects if Autonomy in Joining and Legitimation of Succession on the Family Company Successor’s Commitment - Saputra, Teddy; Padmawidjaja, Liestya; Putri, Dominica Prima Kurnia Kharismatika (Jurnal Entrepreneur dan Entrepreneurship, 2023)
The purpose of this research is to study empirically the effect of autonomy in joining and legitimation of succession towards successors’ commitment to a family business. This research is conducted with a sample of 109 successor family businesses at the UC Family Business Community. The research shows that autonomy or the freedom in making choices has a significant effect on forming affective commitment, while legitimation also has a significant influence at a lower level. Autonomy in joining or freedom in making choices has a significant effect to form normative commitment, while legitimation of succession also has a significant effect at a lower level. Thestudy further shows that legitimation must be supported by autonomy to form an affective commitmentto the successor.